Research for the Development of Crack in Bimetal Al/Cu Sheet - Nguyen, Hữu Hải Quan; Tran, Hưng Trà; Phan, Thanh Nhàn (Journal of Technical Education Science, 2022)
At present, bonding two dissimilar metal materials is a major challenge for today's industries. Applying friction-stirring welding technology is also a feasibility study, but in order to evaluate the bond strength compared to the base material, it is necessary to survey, experiment, evaluate to find out the advantages and disadvantages of this method. In this paper, we only focus on studying the crack development based on force application. In which, this study uses force to make cracks form and develop differently. Specifically, the research focuses on the following contents: surveying the microstructure of the Al/Cu junction, investigating the crack growth. Through this study, we can see how the crack develops, the material of the junction, in addition to the results of the strength of the weld, so that it can be applied effectively, most in practice. When this research experiment performs the crack at different positions according to the standard, applying force to the weld immediately shows that the crack is likely to develop along with the interface between the two materials with the highest ratio and not branched. Thus, this study found that the weld with the higher breaking energy, the higher the bonding strength of the two materials.